Analysis and prediction of vulnerability in smart power transmission system: A geometrical approach. (January 2018) - Gupta, Sudha; Kazi, Faruk; Wagh, Sushama; Singh, Navdeep
Highlights: Hidden geometry of current flow path has been used for contingency analysis. Auxiliary Grid is constructed to apply geometrical concept on power network. The PFI & VI indices have been defined from geometry of current flow path. PFI analyze line condition locally, whether line is under loaded or overloaded. Global analysis has been realized by VI index. Probability of next tripping line and vulnerability centre identified by VI index. Low computational effort as it avoids traditional AC or DC load flow equations. PFI & VI indices have been verified using bench mark IEEE 30 bus power system. Abstract: The paper proposes a novel methodology to analyze and measure the impact of line tripping on grid vulnerability which may lead to cascade failure in smart power transmission system. The key contributions are analysis of current flow path and identification of critical line from normal to perturbed grid with the knowledge of grid topology. To achieve this two performance indices i.e. power flow index and vulnerability index have been defined on the bases of geometry of current flow path. A power flow index is defined to analyze impact of topological changes on current flow path and identify underloaded and overloaded lines. Probability of the critical line and the location of vulnerability center are identified by the vulnerability index. Analytically defined performance indices are applied analyzed and validate using the benchmark IEEE 30 bus power system. The critical line identified by proposed indices is also verified with the probabilistic framework. The proposed methodology allows to focus attention on the power grid vulnerable areas and can help the control system operator to investigate the changes in power flow on transmission lines and initiate the necessary corrective action. The methodology proposed in this paper can be used in security assessment and centralized monitoring of power flow in future smart grid wide area monitoring protection and control system.